Studi Pembuatan Pupuk Organik Cair Dari Sampah Organik Rumah Tangga - Solikhah R (Journal of Environmental Engineering and Waste Management, 2021)
Abstract. Organic waste processing that has not received more attention and awareness has made the generation of organic waste higher in landfills. One of the ways that can be done to reduce waste generation from the source is by composting. The composer is a simple tool that can be used to compost anaerobically with the help of an EM4 activator to speed up the composting process. Objectives: The purpose of this study was to determine whether the parameters of the liquid organic fertilizer produced had met the standards of the Minister of Agriculture Regulation Number 261 of 2019. Method and results: This study used an experimental method with one treatment, namely fermentation time, 14 days and 20 days. The EM4 dose used for all samples was 60 ml per composter. before use EM4 is activated first by providing a food source in the form of a molasses solution of about 600 ml. Sampling was carried out on the 14th and 20th days, then taken to the Sucofindo Cibitung Laboratory to test the Nitrogen, P2O5, and K2O parameters. Based on hypothesis testing with t test, the content of Nitrogen, P2O5, and K2O were not complied with the standard from Decree of the Minister of Agriculture of the Republic of Indonesia Number 261 of 2019. Conclusion: The parameter of Nitrogen,P2O5 and K2O of organic fertilizer produced does not comply with the starndard of Ministerial Decree of Agriculture No. 216 of 2019.